1999
DOI: 10.1046/j.1365-2427.1999.00403.x
|View full text |Cite
|
Sign up to set email alerts
|

Pectoral fin size in a fish species with paternal care: a condition‐dependent sexual trait revealing infection status

Abstract: Summary 1. The three‐spined stickleback, Gasterosteus aculeatus L., is a territorial fish with exclusive male parental care. Males oxygenate the eggs with fanning movements of their pectoral fins. The present authors investigated whether the apparent sexual differences in the functional demands of the pectoral fins have resulted in sexual differences in fin size. If males have relatively larger pectoral fins, females may use this as a signal to aid their mate choice for good fathers. Therefore, further objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
4

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 26 publications
1
34
4
Order By: Relevance
“…Both SL and sex had significant effects (sex: F = 14.532, P < 0.001, df = 553; SL: F = 2660.951, P < 0.001, df = 553). However, in contrast to what was found by Brønseth and Folstad (1997) and by Bakker and Mundwiler (1999), females had significantly larger fins than males when controlling for body size (least square mean ! SE: females = 11.346 !…”
Section: Phenotypic Traitscontrasting
confidence: 82%
See 1 more Smart Citation
“…Both SL and sex had significant effects (sex: F = 14.532, P < 0.001, df = 553; SL: F = 2660.951, P < 0.001, df = 553). However, in contrast to what was found by Brønseth and Folstad (1997) and by Bakker and Mundwiler (1999), females had significantly larger fins than males when controlling for body size (least square mean ! SE: females = 11.346 !…”
Section: Phenotypic Traitscontrasting
confidence: 82%
“…Nest location is thought to influence the predation risk affecting both the embryos and the guarding male (FitzGerald 1983;Mori 1994;Kraak et al 1999a). Based on findings of a sexual dimorphism where males had larger pectoral fins then females and considering that pectoral fins are used in parental care, several authors suggested that this trait could also be involved in mate choice (Brønseth and Folstad 1997;Bakker and Mundwiler 1999;Kü nzler and Bakker 2000). Larger body size has been associated with increased vigor in parental care, including in threespine stickleback (Cô té and Hunte 1989;Wiegmann and Baylis 1995;Kraak et al 1999b), and there are also reports of size assortative mating in this species (Kraak and Bakker 1998;McKinnon et al 2004).…”
mentioning
confidence: 99%
“…Because parental males actively defend their nest from intrusions by cuckolder males during spawning, it is likely that parentals with less energy are less able to thwart intrusions. In sticklebacks, parasite infection by Pomphorhynchus laevis (Acanthocephala) has similarly been reported to be negatively correlated with energy reserves and subsequently reproductive success (Bakker & Mundwiler 1999). The Acanthocephala (Leptorhynchoides sp.)…”
Section: Resultsmentioning
confidence: 99%
“…The dual use of pectoral fins in locomotion and parental care likely makes high functional demands on the size and the shape of the pectoral fins. The size of the pectoral fins is sexually dimorphic in three-spined sticklebacks, with males having larger fins than females during the breeding season (Bakker and Mundwiler, 1999). Pectoral fin size affects paternal quality, as demonstrated by an experimental reduction of fin size leading to extended time required for the young to hatch (Kü nzler and Bakker, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…However, reliable information about fin morphology might be obtained through correlated traits such as the courtship dance, which involves repeated abrupt changes of speed and direction and thus may be influenced by pectoral fin asymmetry. Moreover, during a courtship sequence, males regularly visit their nest to perform behaviours pertinent to parental care, including fanning (Sevenster, 1961;Bakker and Mundwiler, 1999). Males thereby presumably deceive females by pretending to have eggs in their nest, as females preferentially spawn in nests that already contain eggs (Goldschmidt et al, 1993), but may alternatively advertise parental ability and/or individual heterozygosity to choosy females.…”
Section: Discussionmentioning
confidence: 99%